2000
DOI: 10.1590/s0100-879x2000000400012
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction modulation by extracellular signaling molecules: the thymus model

Abstract: Gap junctions are intercellular channels which connect adjacent cells and allow direct exchange of molecules of low molecular weight between them. Such a communication has been described as fundamental in many systems due to its importance in coordination, proliferation and differentiation. Recently, it has been shown that gap junctional intercellular communication (GJIC) can be modulated by several extracellular soluble factors such as classical hormones, neurotransmitters, interleukins, growth factors and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Specifically, the glycocalyx has been shown to play a role in mechanosensing of smooth muscle cells and fibroblasts of the vascular system (Ainslie, Garanich et al 2005, Tarbell and Pahakis 2006, Shi and Tarbell 2011), and may be a relevant mechanism in the synovium during OA as changes occur to the interstitial matrix. Other work investigating the mechanisms addressed in this study already provide examples of potential strategies for controlling mechanosensitivity, such as manipulation of primary cilia length (Ou, Ruan et al 2009, Besschetnova, Kolpakova-Hart et al 2010) and gap junctional communication (Alves, Nihei et al 2000, Kurtenbach and Zoidl 2014). As such, we anticipate that a better understanding of these mechanisms will not only shed light on how the pathological sensitization of FLS to shear stress observed here contributes to the pathophysiology of OA, but point to therapeutic interventions that restore normal mechanosensitivity and hinder progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the glycocalyx has been shown to play a role in mechanosensing of smooth muscle cells and fibroblasts of the vascular system (Ainslie, Garanich et al 2005, Tarbell and Pahakis 2006, Shi and Tarbell 2011), and may be a relevant mechanism in the synovium during OA as changes occur to the interstitial matrix. Other work investigating the mechanisms addressed in this study already provide examples of potential strategies for controlling mechanosensitivity, such as manipulation of primary cilia length (Ou, Ruan et al 2009, Besschetnova, Kolpakova-Hart et al 2010) and gap junctional communication (Alves, Nihei et al 2000, Kurtenbach and Zoidl 2014). As such, we anticipate that a better understanding of these mechanisms will not only shed light on how the pathological sensitization of FLS to shear stress observed here contributes to the pathophysiology of OA, but point to therapeutic interventions that restore normal mechanosensitivity and hinder progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the involvement of gap junctions in the communication between cells of the immune system [17][18][19][20][21][22][23][24]. Indirect evidence for the importance of gap junctions in immunity comes from the observation that viruses -such as herpes simplex virus (HSV) and human papillomavirus (HPV) -actively influence gap junction communication [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Gap junctional intercellular communication can be modulated by several extracellular soluble factors such as classical hormones, neurotransmitters, interleukins, growth factors and some paracrine substances (Alves et al, 2000a). Activation of either voltage-or receptor-operated channels may modulate function of gap junctions and therefore transfer of signaling molecules through them.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work suggests that there is not an easy answer to the questions of whether gap junctions can be mediators/ wave via gap junctional intercellular communication (GJIC) forms the spreading depression leading to the expansion of stroke volume. Gap junctional intercellular communication can be modulated by several extracellular soluble factors such as classical hormones, neurotransmitters, interleukins, growth factors, and some paracrine substances (Alves et al, 2000a). Activation of either voltage-gated channels or receptor-operated channels (e.g., glutamate) may modulate function of gap junctions and therefore transfer of signaling molecules through them.…”
Section: Controversial ''Protectant'' or ''Bystander Cell Killing'' Rmentioning
confidence: 99%